Raman scattering in carbon nanotubes - Shiri, Pricciard Roy (My University, 2009)
Analysis of peak shifts of Raman vibrational modes in single-walled carbon nan- otubes (SWCNTs) gives important information about the vibrational properties of SWCNTs, which in turn gives a deeper understanding of the physical, electronic and thermal properties of SWCNTs. In this work, the temperature dependence of the frequencies and linewidths of the vibrational modes of semi-conducting and metallic nanotubes were studied using Raman spectroscopy. The SWCNTs used here were synthesized using the electric- arc discharge method. Two laser lines, the 514.5 nm and 488.0 nm were used to exploit the resonances of the semi-conducting tubes and the 647.1 nm was used to excite metallic SWCNTs. The radial breathing mode (RBM) peak positions of semi-conducting and metal- lic tubes were observed to decrease at di®erent rates with increasing temperatures. The line shapes of the RBMs also change signi¯cantly with changes in temperatures. The G+ and G¡ peaks of the tangential modes (G-band) of semi-conducting and metallic nanotubes also decrease at di®erent rates with increasing temperatures. A comparison of the rates of change of mode frequency of the G+ and G¡ modes in metallic and semi-conducting nanotubes gives more insight into the role played by electron-phonon coupling and plasmon-phonon coupling in each case. It gives a deeper insight into the contentious issue of mode assignment of the G+ and G¡-modes of metallic SWCNTs.